2005
DOI: 10.2337/diabetes.54.11.3073
|View full text |Cite
|
Sign up to set email alerts
|

Inositol (1,4,5)-Trisphosphate Dynamics and Intracellular Calcium Oscillations in Pancreatic β-Cells

Abstract: Glucose-stimulated insulin secretion is associated with transients of intracellular calcium concentration ([Ca2؉is an important signaling mechanism in the glucose-stimulated ␤-cell (10,11). ␤-Cells have been shown to contain inositol 1,4,5-trisphosphate [Ins(1,4,5)P 3 ] receptors (12), ryanodine receptors (4,10), and Ca 2ϩ channels gated by cyclic ADP-ribose (13) or nicotinic acid adenine dinucleotide phosphate (14,15). Ins(1,4,5)P 3 -dependent mobilization of endoplasmic reticulum Ca 2ϩ has been well describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 45 publications
3
52
0
Order By: Relevance
“…Real-time imaging studies in isolated insulinoma cells and intact islets (Thore et al, 2004;Tamarina et al, 2005;Thore et al, 2007) have recently confirmed that glucose stimulates PLC activity secondary to the elevation of [Ca 2+ ] i and that membrane depolarization alone (Gromada et al, 1996;Liu et al, 1996) or increase of [Ca 2+ ] i (Mathias et al, 1985;Best et al, 1987;Biden et al, 1987) In addition to contributing to the generation and shaping of Ca 2+ signals, PLC activation can be anticipated to regulate insulin secretion kinetics via generation of DAG and activation of PKC. Several conventional, novel and atypical PKC isoforms are expressed in islets and insulin-secreting cells (Jones and Persaud, 1998;Warwar et al, 2006).…”
Section: Pip 2 and Signalling Via Phospholipase Cmentioning
confidence: 97%
“…Real-time imaging studies in isolated insulinoma cells and intact islets (Thore et al, 2004;Tamarina et al, 2005;Thore et al, 2007) have recently confirmed that glucose stimulates PLC activity secondary to the elevation of [Ca 2+ ] i and that membrane depolarization alone (Gromada et al, 1996;Liu et al, 1996) or increase of [Ca 2+ ] i (Mathias et al, 1985;Best et al, 1987;Biden et al, 1987) In addition to contributing to the generation and shaping of Ca 2+ signals, PLC activation can be anticipated to regulate insulin secretion kinetics via generation of DAG and activation of PKC. Several conventional, novel and atypical PKC isoforms are expressed in islets and insulin-secreting cells (Jones and Persaud, 1998;Warwar et al, 2006).…”
Section: Pip 2 and Signalling Via Phospholipase Cmentioning
confidence: 97%
“…Whereas several studies indicate that the glucoseinduced phosphoinositide hydrolysis depends on the presence of extracellular Ca 2ϩ (9,11,12), other reports indicate that the process is at least in part Ca 2ϩ independent (13)(14)(15). Recent observations in single insulinoma cells (16) and intact mouse islets (17) have demonstrated that elevation of [Ca 2ϩ ] i is sufficient to trigger PLC activity and that [Ca 2ϩ ] i oscillations are associated with periodic activation of PLC. However, the kinetics of the early changes in PIP 2 concentration and how it is related to [Ca 2ϩ ] i after glucose stimulation are unknown.…”
mentioning
confidence: 99%
“…The extent of ␤-cell depolarization and insulin release are regulated in part by the activation of repolarizing ion channels, including the voltage-gated potassium channel, Kv2.1 (2)(3)(4). One mechanism employed by pancreatic ␤-cells to regulate the biophysical activity of the ion channels involved in insulin release involves hydrolysis of membrane phospholipids to yield mediators that include inositol triphosphates and free fatty acids (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Pharmacologic, biochemical, and genetic evidence suggests that glucose-stimulated hydrolysis of esterified arachidonic acid from ␤-cell membrane phospholipids is required for physiological insulin secretion (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Pancreatic islet ␤-cells contain high levels of arachidonic acid compared with other tissues (7, 9 -12 24, 25), and about two-thirds of islet ␤-cell glycerophospholipids contain arachidonic acid as the sn-2 substituent (23)(24)(25).…”
mentioning
confidence: 99%